2020
DOI: 10.3390/genes11070731
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Comparative Analysis of Myosin Gene Family in Four Major Cotton Species

Abstract: Myosin protein as a molecular motor, binding with Actin, plays a significant role in various physiological activities such as cell division, movement, migration, and morphology; however, there are only a few studies on plant Myosin gene family, particularly in cotton. A total of 114 Myosin genes were found in Gossypium hirsutum, Gossypium barbadense, Gossypium raimondii, and Gossypium arboreum. All Myosins could be grouped into six groups, and for each group of these genes, similar gene structures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…These proteins were split into six subgroups by the phylogenetic tree, indicating great divergence between these members. Various researchers supported our results in other crops such as Nicotiana tobacco ( Amari et al., 2014 ) and Gossypium hirsutum ( Ma et al., 2020 ). Motif analysis showed that most of the motifs were preserved in a group, suggesting that these motifs were of similar evolutionary origin.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These proteins were split into six subgroups by the phylogenetic tree, indicating great divergence between these members. Various researchers supported our results in other crops such as Nicotiana tobacco ( Amari et al., 2014 ) and Gossypium hirsutum ( Ma et al., 2020 ). Motif analysis showed that most of the motifs were preserved in a group, suggesting that these motifs were of similar evolutionary origin.…”
Section: Discussionsupporting
confidence: 89%
“…Bioinformatics tools are also helpful to discover the interaction among macromolecules, distribution of protein properties, their biological functions ( Ahmad et al., 2020 ) and identification of new capable compounds ( Azeem et al., 2018 ). Myosin proteins belong to a superfamily of molecular motors that binds and hydrolyzes ATP to generate the force and movement along actin filaments ( Bechtel and Bollhagen, 2021 ; Ma et al., 2020 ). This force is necessary to drive various cellular functions, cell movement, muscular contraction, cytokinesis, membrane trafficking and signal transduction ( Steffens et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations